Figure–ground relationship of voices in musical structure modulates reciprocal frontotemporal connectivity - Kim, Chan Hee; Seo, Jeong-Eun; Seol, Jaeho; Chung, Chun Kee (Frontiers in Neuroscience, 2026)
When listening to polyphonic music, we often perceive a melody as the figure against the ground of accompanying sounds. However, with repeated exposure, this figure–ground relationship may naturally shift, allowing the melody to recede into the ground. In a previous study, we found the consistent pattern of frontotemporal connectivity for the “Twinkle, Twinkle, Little Star” (TTLS) melody in the headings of two Variations (II and IV) in Mozart's 12 Variations, K. 265, indicating that the TTLS melody, but not the different lower voices, was the figure. However, the frontotemporal connectivity pattern may change in the same phrases repeating in the two variations. In the current study, we examined how frontotemporal connectivity changes in the repeated phrases. In the results, the frontotemporal connectivity pattern between the two variations changed in the final phrase after repeated passages. This suggests that the shift in the figure–ground relationship persists, with the TTLS melody becoming less prominent while the lower voices become relatively more prominent. Additionally, frontotemporal connectivity was strongly correlated with temporofrontal connectivity in the opposite direction. Finally, our data indicate that TTLS melody-based and sensory-based processes in response to a switched figure–ground relationship, are incorporated into the bidirectional connections between frontotemporal and temporofrontal connectivity. Our study highlights the brain's ability to reconfigure figure–ground relationships in the processing of musical voices.